Onto-ontology methodology for design of ontology-based multi-agent systems - Hadzic, Maja; Chang, Elizabeth (CRL Publishers, 2008)
Multi-agent system provides a distributed collaborative platform and characterizes the system dynamics. Ontologies represent the domain knowledge and can be used to support various processes within a multi-agent system. Ontologies are high expressive knowledge models and as such increase the expressiveness and intelligence of a system. We propose onto-agent methodology for design of ontology-based multi-agent systems, as the first methodology that unifies the different approaches of the existing ontology and multi-agent systems design methodologies. Onto-Agent Methodology is composed of the two interconnected processes: ontology design process and multi-agent system design process. Each of the two design processes is composed of five steps. We discuss each of the steps separately and provide some illustrative examples.